Some applications of the novel numerical methods - İnç, Mustafa; Akgül, Ali (American Institute of Physics Inc., 2018)
[Abstract Not Available]
International Conference of Numerical Analysis and Applied Mathematics, ICNAAM 2017 -- 25 September 2017 through 30 September 2017 -- Thessaloniki -- 137831